The Effect of Tariffs, Working Hours, and Location on Maxim Drivers' Income in Rantauprapat City - Gilang Ananda Abdila; Bayu Eko Broto; Abdillah Menri Munthe (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
His research attempts to examine how location, working hours, and tariffs affect Maxim drivers' earnings in Rantauprapat City. In this study, 75 respondents were chosen at random using an associative method and a quantitative approach. A Likert-scale questionnaire was used to gather the data, and SPSS multiple linear regression was used for analysis. The findings demonstrated that while tariffs and location had no discernible impact on drivers' income, working hours had a favorable and considerable impact. All factors had a considerable impact on drivers' income at the same time. According to the coefficient of determination (R2) value of 0.383, the independent variables account for 38.3% of the variation in income, with additional factors outside the research model influencing the remaining portion.